Analisis dampak meditasi terhadap kemampuan peserta didik usia sekolah dasar dalam mengelola emosi diri - Hasan Mahfud; Roy Ardiansyah; Putri Nur'Aini (Universitas Sebelas Maret, 2022)
Abstract. This Study aims to describe theimpact of meditation on the ability of elementary school-age students in managing self-emotion. The way to overcome emotional control so that it can improve emotional intelligence in children is through meditation. Meditatin has a positive effect on individual emotions. In this study, the subjects to be studied were e fifth-grade students of SD Masjid Syuhada Yogyakarta with total of 12 students. The method use in this researc is descriptive qualitative with a case study approach. The research subject was taken by using the purposive sampling technique. The data sources of this research were meditation guides and grade V students of SD Masjid Syuhada Yogyakarta. The data were collected through observation and interview. The data validation used source triangulation and techincal triangles. Data analysis was performed throughdata reduction techniques, data presentation, and concluding. The results showed that meditation had a positive impact on students' ability to manage their emotions. This is indicated by increased self-confidence, emotional prowess, the ability to manage emotions in the classroom, and being able to express feelings.